Geodetic evaluation of terrain surface subsidence around mine shifts of KWK Bogdanka in 1976-1983 - Borowski, Witold; Zyga, Jacek (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
An attempt to apply a measuring dynamic network model into land subsidence process evaluation is described in the presented essay. The surface subsidence process, occurring on rural areas around KWK Bogdanka, is suspected to be consequent upon orogen drainage, related to drilling of mining shafts. The elaboration of archival measuring data with the use of a dynamic model of measuring network enabled to extend the interpretation extension of the interpretation of the observed settlements process for potential drainage process parameters, affecting a specific rock deformation process.